Enhancing nutrient use and sugarcane (Saccharum officinarum) productivity with reduced cost through drip fertigation in western Maharashtra - PAWAR, D D; DINGRE, S K; DURGUDE, A G (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at Interfaculty Department of Irrigation Water Management, Mahatma Phule Krishi Vidyapeeth, Rahuri (Maharashtra) during three consecutive years 2007-2010 to study the yield, nutrient use and cost economics for sugarcane (Saccharum officinarum L.) cultivation under different fertigation schedules. The experiment comprised 100, 80 and 60 per cent water soluble fertilizers (WSF) applied through drip in two schedules and results were compared with three control treatments. The 100 per cent fertigation as per growth stages (schedule B) showed higher cane yield (187.85 tonnes/ha) and sugar yield (22.00 tonnes/ha); however, it was on par with 100% fertigation in uniform equal splits (schedule A) and 80% fertigation (schedule B). The study indicated that drip irrigation resulted into 25 % increase in sugarcane yield whereas drip with fertigation resulted into 42 % increase in yield as compared to conventional method. Application of water soluble fertilizers had positive effect on periodical availability of nutrients and uptake than conventional fertilizer. The higher net seasonal income (Rupees 226 195 per ha) and net extra income over conventional method (Rupees 66 246 per ha) were obtained in 100 % fertigation as per schedule B however, the economical parameters were on par with 100 % fertigation as per schedule A and 80% fertigation as per schedule B. The application of 80 % water soluble fertilizers as per schedule B through drip irrigation was found best practice to obtain better yield, improve nutrient and water use as well as cost economics among the practices studied.